Responsible tourism development-A systematic review & bibliometric analysis - P. G. S. S. Pattiyagedara; J. P. R. C. Ranasinghe (Goodwood Publishing, 2023)
Purpose: This study aims to systematically review and conduct a bibliometric analysis of the literature on Responsible Tourism development using articles published between 2002 and 2023. Research Methodology: Systematic literature review (SLR) was conducted using established databases using preferred reporting items for systematic review meta-analysis (PRISMA) guidelines, and Vosviwer software was employed to identify key trends, themes, and contributors in the field. Results: The review identified a growing body of literature on Responsible Tourism and found key phrases in scientific publications, predominantly on Responsible Tourism development: 71 articles were included from Lens.ORG, Emerald Insight, and Google Scholar databases, all of which were formatted for Lens. ORG. The two main themes were (1) economic development-related outcomes and (2) sustainability of tourism-based outcomes. The findings imply that future study trends should focus on sustainable outcomes such as responsible tourism development. A bibliometric analysis revealed a network of authors and their notable contributions from both academia and industry. Limitations: The study was limited by the availability of literature in the searched databases and the scope of the review over a considerable period. Contributions: Understanding responsible tourism development by providing a comprehensive overview of the literature and illustrating key trends and themes is the major contribution of this study. It also highlights the need for further research in certain areas regarding the role of technology in responsible tourism development and enhancing residents’ quality of life.